Civil Liability in the practice of physical activity (Research, Society and Development, 2023)
Narrative review with the objective of analyzing civil responsibilities generated in the consumption relation in the practice of physical activity, in the contracting of the practice of physical activity and who is responsible for civil liability, types of accidents that occurred in these and types of indemnities that occurred. In the analysis of the assumptions of the institute of civil liability, the aim is not to leave damage unrepaired, in a posture of respect for the consumer. In the consumer relationship (consumer, supplier, products or services), a prerequisite for the application of the Consumer Defense Code, civil liability governs relationships that depend on legal regulations, and the supplier of goods or services will respond regardless of fault, for damage caused to the consumer arising from addictions or defects in the products and services offered in the practice of physical activity. It is up to the legislator to have his eyes turned to society, using the instruments that the law places at his disposal, whether in a preventive, punitive or pedagogical way, to realize the ideal of justice.